"Our" food versus "my" food. Investigating the relation between childhood shared food practices and adult prosocial behavior in Belgium. (1st January 2015) - De Backer, Charlotte J.S.; Fisher, Maryanne L.; Poels, Karolien; Ponnet, Koen
Highlights: Mealtimes are an ideal arena for the socialization of prosociality. Previous works mainly focused on the presence of others at the table. Focusing on food, we make a distinction between eating together and sharing meals. Childhood shared meal frequencies correspond to adult prosociality scores. Eating together frequencies do not correspond to adult prosociality scores. Abstract: This study focuses on the connection between prosocial behavior, defined as acting in ways that benefit others, and shared meals, defined as meals that consist of food(s) shared with others. In contrast to individual meals, where consumers eat their own food and perhaps take a sample of someone else's dish as a taste, shared meals are essentially about sharing all the food with all individuals. Consequently, these meals create situations where consumers are confronted with issues of fairness and respect. One should not be greedy and consume most of a dish; instead, rules of polite food sharing need to be obeyed. It is therefore proposed that those who have often engaged in shared meals during childhood will have a more prosocial personality, as compared to those who less often took part in shared meals during childhood. To test this hypothesis, data about frequency of shared meals during childhood and altruistic personality in early adulthood were collected using a cross-sectional survey in Belgium ( n = 487). Results confirm that higher levels of shared meal consumption correspond to higher scores on the self-report altruism scale among students.